Virulence of Pyrenophora teres populations in western Canada. Issue 2 (2nd April 2016) - Akhavan, Alireza; Turkington, T. Kelly; Askarian, Homa; Tekauz, Andy; Xi, Kequan; Tucker, James R.; Kutcher, H. Randy; Strelkov, Stephen E.
Abstract: Net blotch, caused by Pyrenophora teres, is an economically important disease of barley. The pathogen has two morphologically similar but genetically distinct forms: P. teres f. teres ( Ptt ) and P. teres f. maculata ( Ptm ), which cause net form net blotch (NFNB) and spot form net blotch (SFNB), respectively. The virulence of a collection of 39 Ptt and 27 Ptm isolates collected from western Canada was evaluated by inoculating these isolates onto sets of barley differential hosts. One week following inoculation, the second and third leaves of each plant were rated for disease severity on scales of 1–10 (for Ptt ) or 1–9 (for Ptm ). Plants rated <5 and ≥5 were scored as resistant and susceptible to Ptt, respectively, while plants rated 1–3 and >3 were scored as resistant and susceptible to Ptm . The experiment was repeated. Cluster analysis revealed 16 and 13 distinct pathotype groups, respectively, among the 39 and 27 representative Ptt and Ptm isolates. The barley differentials CI 5791 and CI 9820 were resistant to all isolates of Ptt except one, whilst the differential CI 9214 was resistant to all isolates of Ptm except two. Therefore, the differential lines CI 5791 and CI 9820, for Ptt, and CI 9214, for Ptm, can still be considered as potentially useful sources of resistance for Canadian barley breeding programmes.